El Puerto de La Laja (Huelva), como Bien de Interés Cultural en la categoría de Sitio Histórico - Emilio Romero Macías; Juan M. Pérez López (PASOS Revista de Turismo y Patrimonio Cultural, 2010)
The Harbor of La Laja, it is a real example of recovery architecture of an ancient miner village for rural tourism exploitation. It is one of the possible bases of actions in the region of mines of the province of Huelva, to offer an alternative to sun and beach tourism, for knowledge of other cultures and as a development plan of areas that have been affected by the decline of mining in our province. Part of the village of the Harbor of La Laja has been currently restored for its exploitation for rural tourism, which is why the architecture in a way has tried to coordinate former arrangement of houses with fulfilled improvements for this type of use.